2015
DOI: 10.1007/s00429-015-1072-1
|View full text |Cite
|
Sign up to set email alerts
|

Axonal elongation and dendritic branching is enhanced by adenosine A2A receptors activation in cerebral cortical neurons

Abstract: Axon growth and dendrite development are key processes for the establishment of a functional neuronal network. Adenosine, which is released by neurons and glia, is a known modulator of synaptic transmission but its influence over neuronal growth has been much less investigated. We now explored the action of adenosine A2A receptors (A2AR) upon neurite outgrowth, discriminating actions over the axon or dendrites, and the mechanisms involved. Morphometric analysis of primary cultures of cortical neurons from E18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 88 publications
(109 reference statements)
2
23
0
2
Order By: Relevance
“…More specifically, we observed that newborn GABAergic neurons exhibited both smaller soma and dendritic fields in K252a-treated animals, whereas these cells exhibited a larger soma surface with enhanced dendritic branching in the UVN-BDNF group. Axon growth and dendrite development are key processes for the establishment of a functional neuronal network and it was reported recently that dendritic branching is BDNF dependent (Ribeiro et al, 2015). Together, our results demonstrate that BDNF action through TrkB receptors amplifies cell proliferation, survival, and development of functional dendritic branching in the deafferented VN of the vestibular-lesioned cats.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…More specifically, we observed that newborn GABAergic neurons exhibited both smaller soma and dendritic fields in K252a-treated animals, whereas these cells exhibited a larger soma surface with enhanced dendritic branching in the UVN-BDNF group. Axon growth and dendrite development are key processes for the establishment of a functional neuronal network and it was reported recently that dendritic branching is BDNF dependent (Ribeiro et al, 2015). Together, our results demonstrate that BDNF action through TrkB receptors amplifies cell proliferation, survival, and development of functional dendritic branching in the deafferented VN of the vestibular-lesioned cats.…”
Section: Discussionsupporting
confidence: 78%
“…Here, we show that continuous BDNF administration into the fourth ventricle after UVN significantly increases the production of newly generated cells, confirming the proneurogenic properties of this growth factor in vivo. Similarly, a previous study showed that BDNF infusion into the lateral ventricle of the adult rat leads to new neurons in the striatum, septum, thalamus, and hypothalamus (Pencea et al, 2001). Next, we used K252a and showed that it strongly attenuated the proneurogenic action of UVN.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations